2004
DOI: 10.1099/vir.0.79805-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small-animal and primate models for evaluation of vaccine candidates for human metapneumovirus (hMPV) and implications for hMPV vaccine design

Abstract: Human metapneumovirus (hMPV), a recently identified paramyxovirus, is the causative agent of respiratory tract disease in young children. Epidemiological studies have established the presence of hMPV in retrospective as well as current clinical samples in Europe, USA, Canada, Hong Kong and Australia. The hMPV disease incidence rate varied from 7 to 12 %. This rate of disease attack places hMPV in severity between respiratory syncytial virus and human parainfluenza virus type 3, two common respiratory pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 28 publications
5
123
2
1
Order By: Relevance
“…For instance, MacPhail et al observed low hMPV titers in the lungs of BALB/c mice and cotton rats, following an intranasal challenge of 10 6 PFU (i.e., 10 2.4 and Ͻ10 1.8 PFU/g of lung, respectively, on day 4 postinfection) (28). Furthermore, no clinical signs were observed in those animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, MacPhail et al observed low hMPV titers in the lungs of BALB/c mice and cotton rats, following an intranasal challenge of 10 6 PFU (i.e., 10 2.4 and Ͻ10 1.8 PFU/g of lung, respectively, on day 4 postinfection) (28). Furthermore, no clinical signs were observed in those animals.…”
Section: Discussionmentioning
confidence: 99%
“…The two paramyxoviruses have been associated with bronchiolitis and pneumonia in young children (9,17,23,48). Although some primates are permissible to hMPV (26,28,42) and hRSV (11) infections, we selected to study BALB/c mice and cotton rats as possible experimental models for hMPV infection because those small animals are considered useful and practical models for characterizing the pathogenesis of hRSV infection and for evaluating therapeutic and prophylactic approaches (7, 11, 12, 19, 22, 24, 33, 38, 39, 41, 45, 46, 50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ability to co-infect with other respiratory infectious agents, including RSV and pneumococci [14,27], combined with its relatively slow replication in cell culture likely accounted for its ability to escape isolation until 2001. Various animal models have been utilized to study hMPV infection including mice, hamsters, and several species of primates [10,12,13,23]. Recent studies indicate that infection of cotton rats with hMPV is associated with efficient viral replication in the lung and reproducible pulmonary pathology [10,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…The replication properties of hMPV in the respiratory tract of AGMs were described elsewhere (26). The daily mean replication titers showed that b/h PIV3 RSV F2 and b/h PIV3/sol RSV F2 achieved peak virus titers of ϳ5 log 10 in the URT on day 4 postimmunization (Fig.…”
Section: Recombinant B/h Piv3 Expressing Native or Soluble Rsv F Protmentioning
confidence: 99%